Exploration on the use of learning strategies in writing for English major students - Pang, Yifan; Hashim, Harwati; Said, Nur Ehsan Mohd (Nurture, 2024)
Purpose: This study delves into the intricacies of writing learning strategies and systematically assesses their use. Design/ Methodology/ Approach: By using quantitative methods, which include systematic questionnaires and CET-6 tests (CET stands for “College English Test,” a standardized English proficiency exam in China), this study collected a large amount of data to gain an in-depth understanding of the overall use of writing learning strategies. The study also examined the use of these strategies in colleges and universities at different levels, as well as the differences in strategy use by learners of different genders. Finding: The study reveals that English major students utilize cognitive, metacognitive, and social-affective strategies to enhance their writing skills, with metacognitive strategies like planning and self-monitoring being particularly effective. However, challenges such as time management, motivation, and lack of guidance hinder effective implementation. Conclusion: Significant differences were found in the use of metacognitive strategies among Chinese students, indicating their infrequent use in English writing. These findings suggest the need for targeted interventions to improve strategy application. Implications: This study aims to provide a more in-depth and empirical understanding of writing education and to offer a strong basis for educational practice and policy-making. It seeks to offer practical writing teaching suggestions for educators to promote students’ all-around development in writing.